Efektifitas Model Pembelajaran Kooperatif dalam Meningkatkan Partisipasi Siswa Kelas VII Dalam Pembelajaran Agama Katolik di SMPK Swadaya Tuakepa - Theresia Paulina Nogo L. Makin; Yoseph Lodowik D. Dau; Emilia Dolorosa Taek (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to determine the effectiveness of implementing the cooperative learning model in improving the participation of seventh-grade students in Catholic Religious Education and to identify the factors that support and hinder its implementation. This study employed a descriptive qualitative approach, which focuses on gaining an in-depth understanding of students' experiences, perspectives, and engagement in the learning process. Through this approach, the researcher sought to examine how the implementation of the cooperative learning model encourages students to participate more actively in Catholic Religious Education classes at SMPK Swadaya Tuakepa. Based on the results of interviews, observations, and documentation, the findings revealed that the implementation of the cooperative learning model significantly increased students' participation in the learning process. Students became more active in group discussions, asking and answering questions, expressing their opinions, collaborating with their peers, and participating in various classroom learning activities. The cooperative learning model also helped create a more engaging, interactive, and conducive learning environment, which enhanced students' learning motivation. However, several challenges were identified, including differences in students' abilities, a lack of self-confidence among some students, and limited instructional time. Nevertheless, overall, the cooperative learning model proved to be effective in improving the participation of seventh-grade students in Catholic Religious Education at SMPK Swadaya Tuakepa.